If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 8) + -11 = 7 Reorder the terms: 3(8 + 3x) + -11 = 7 (8 * 3 + 3x * 3) + -11 = 7 (24 + 9x) + -11 = 7 Reorder the terms: 24 + -11 + 9x = 7 Combine like terms: 24 + -11 = 13 13 + 9x = 7 Solving 13 + 9x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 9x = 7 + -13 Combine like terms: 13 + -13 = 0 0 + 9x = 7 + -13 9x = 7 + -13 Combine like terms: 7 + -13 = -6 9x = -6 Divide each side by '9'. x = -0.6666666667 Simplifying x = -0.6666666667
| 120=2x | | 2(3x+8)=7 | | -55-(-42+7)= | | y^2-9y-11=0 | | (x-2)2+(x+1)2=0 | | x+(x+27)=123 | | 2/3(d+9)=-12 | | x-7.2=3.8 | | (4xy+3y^4)dx+(2x^2+5xy^3)dy=0 | | 12s+6=6s-4 | | (1/2)x+3=4 | | 21m-11=10 | | 4(x+2)=x+17 | | -10=109(K-9) | | 3x^2+42x+147= | | 4x+12=3x-8 | | 6x^2+5ab-6b^2=0 | | f=2 | | 3x+2=234 | | 25+3=(10x-36) | | -4x+3=13 | | 2e+6=5e+9 | | x=-0.4x+7 | | X=12Z+Zt | | -8x-(2x+3)=6x+5 | | 3ln(4x+8)=16 | | Y=5x^2+3x+9 | | 5(x-3)+3(x+2)=7x | | X=2P(Y+4) | | 2x*2x*2x*4x=128 | | 22-4n=74 | | -8x+2(6x-2)=-8x-4(2x+16)-x |